MOTIVASI KERJA KARYAWAN PT. GS ELECTECH INDONESIA: FAKTOR KOMPENSASI DAN PROMOSI JABATAN - Ida Abdul Gopar (LP2M Sekolah Tinggi Ilmu Ekonomi IPWI Jakarta, 2017)
This research analyze relations compensation and position promotion to motivation work employees the contract to PT. GS Electech Indonesia, data obtained from the questionnaire and direct observation in the field .Data analyzed use linear regression multiple .Research findings shows that compensation as the provision of retribution services consists of financial compensation , Non financial and activity has not been found relationship to motivation work employees the contract to PT. GS Electech Indonesia. Position promotion as a form of recognition of the results of was given based on accomplishments , experience and a mastery work has not been found relationship to motivation work employees the contract to PT. GS Electech Indonesia. This indicates that motivation work employee who seen from conformity over received an incentive , the condition workplace comfortable , received an award , given responsibility work and happy with the work he was doing not prescribed by compensation and position promotion applied a company to an employee contract .Â Keywords:compensation , position promotion and motivation